Scientific, Theoretical and Methodological Foundations for the Development of Information Competence Based on an Innovative Approach to Teachers of Mathematics General Secondary Education - Suyunov Ilkhom Egamberdievich (Research Parks Publishers, 2021)
The article states that a study conducted to determine the effectiveness of modern education shows that the level of achievement of educational goals is measured by the degree of increased mental activity of a student. The organization of the activation of the student's activity in the learning process by the teacher means an independent, active, purposeful study of the educational material, based on the use of methods and techniques of self-government, self-control of students. The form states the purpose of the study